Influence of propulsion installation performance on travel efficiency - Lupchian, Mariana (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
This paper presents an analysis of exploitation parameters for naval propulsion plant at different operating regimes. For naval propulsion plant with internal combustion engines, is considered as independent variables which give its operating regimes. Functional parameters of analysis of navigational regimes considered representative of the operation of the ship. Propulsion of the ship is provided by a fixed pitch propeller that allows modification propulsion performance by adjusting a single parameter function: speed propeller.